2008
DOI: 10.1111/j.1442-2042.2007.01983.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of postoperative inguinal hernia after endoscope‐assisted mini‐laparotomy and conventional retropubic radical prostatectomies

Abstract: Objective:The objective of the present study was to compare the incidence of postoperative inguinal hernia between endoscope-assisted mini-laparotomy retropubic radical prostatectomy (mini-lap RRP) with conventional techniques to identify possible risk factors. Methods: From April 1998 to December 2006, 347 consecutive cases with localized prostate cancer were treated with conventional RRP (75 cases) and mini-lap RRP (272 cases) with pelvic lymphadenectomy. Mini-lap RRP was carried out with a 6-cm median incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…They concluded that IHs were less frequent after a mini-lap RRP than after a conventional RRP. 10 In contrast to the RRP, the abdominal cavity was not entered in a radical perineal prostatectomy (RPP), so it seems reasonable to assume that the risk of developing an IH postoperatively would not be increased. In the series of Matsubara et al, the incidence of IHs after an RPP was 1.8% (5 of 285) with a median follow-up time of 43 months, whereas the incidence of IHs after RRP was 10.3% (32 of 311) with a median follow-up of 36 months (p Z 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that IHs were less frequent after a mini-lap RRP than after a conventional RRP. 10 In contrast to the RRP, the abdominal cavity was not entered in a radical perineal prostatectomy (RPP), so it seems reasonable to assume that the risk of developing an IH postoperatively would not be increased. In the series of Matsubara et al, the incidence of IHs after an RPP was 1.8% (5 of 285) with a median follow-up time of 43 months, whereas the incidence of IHs after RRP was 10.3% (32 of 311) with a median follow-up of 36 months (p Z 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…У 29 (38,7 %) пациентов 1-й группы и у 8 (2,9 %) больных 2-й группы в последующем ди-агностировали образование паховой грыжи. На осно-вании полученных результатов авторы пришли к вы воду, что паховая грыжа чаще развивается после простат-эктомии, выполненной открытом доступом [15].…”
Section: материалы и методыunclassified
“…Since the first report by Regan et al in 1996 [1], the high incidence of postoperative inguinal hernia (IH) has been recognized as a common complication of RRP. The incidence of IH after RRP has been reported to range from 12 % to 38.7 % [1][2][3][4][5][6][7]. Furthermore, reportedly more than 90 % of IH after RRP was indirect hernia [4,6].…”
Section: Introductionmentioning
confidence: 99%